AuAg nanocages/graphdiyne for rapid elimination and detection of trace pathogenic bacteria - Bai, Qiang; Luo, Hongyang; Shi, Shugao; Liu, Shen; Wang, Lina; Du, Fanglin; Yang, Zhugen; Zhu, Zhiling; Sui, Ning (Elsevier, 2022)
We prepared a biocompatible AuAg nanocages/graphdiyne @ polyethylene glycol (AuAg/GDY@PEG) composite. The combination of AuAg and GDY to obtain a synergistically enhanced photothermal effect, and the antibacterial effect of GDY and AuAg are used in combined anti-infective therapy. The in vitro antibacterial activity of AuAg/GDY@PEG was investigated, showing an impressive broad-spectrum antibacterial activity with the killing rate > 99.999%. Based on the photothermal conversion ability of AuAg/GDY@PEG, a simple photothermal immunoassay for pathogenic bacteria was successfully established. Sandwich immune response was performed on a microporous plate, the microplate containing the antibody binds specifically to the bacterium being tested, which then binds to the material with the antibody on its surface, and the signal was a change in temperature under 808 nm near-infrared light. The limit of detection (LOD) for S. typhimurium detection is 103 CFU mL−1, with a range of 103–107 CFU mL−1. This method is accurate, rapid and low-cost, which can be used for on-site detection of pathogenic bacteria in food.
Keywords: Photothermal effect; Gold-silver nanocages; Graphdiyne; Immunoassay; Antibacterial